Nepal Environment Sector Diagnostic : Path to Sustainable Growth Under Federalism - World Bank (World Bank, Washington, DC, 2019)
The 2015 Constitution ushered in not only a comprehensive transformation of Nepal's government structure, but also a shift from a protection-focused approach to natural resources management to one that aims to harness resources sustainably. Nepal's rich water, forest and biodiversity resources would thus fuel economic growth and prosperity and help achieve the goal becoming a middle-income country by 2030.The objective of this Environment Sector Diagnostic (ESD) is to inform policies, investments and institutional capacity building measures in key areas of natural resources use and environmental management to support sustainable growth and prosperity in Nepal in the context of federalism. Thus, the ESD aims to inform investment projects and government policies and facilitate the implementation of the World Bank's new Environmental and Social Framework in the context of the projects it supports.The key themes of natural resource use addressed in the ESD are forest management, nature-based tourism, hydropower development, agricultural intensification, and river quarrying. For each theme, the ESD highlights the economic gains of more productive use of the associated natural resources, where possible through quantitative modelling, and points to investments and policy and institutional measures to ensure sustainability. In terms of adverse environmental impacts, the ESD focuses on pollution, including air pollution, solid waste including hazardous substances, as well as, road construction. It estimates the cost of pollution to the economy and provides recommendations to lower this cost. These themes were selected based on their current and potential role in the economy and their current and potential impact on the environment.